Prognostication of the asymmetry of population incomes in Ukrainian regions - Kostenko Anna; Danyluk Liudmyla (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
The article presents the results of the medium-term forecast of income asymmetry of the population of Ukraine. Of the set of special research methods, statistical analysis was used. The initial information for the forecast was the official statistical data, namely: the income of the population of Ukraine in the dynamics by the type of economic activity and in the regional section over the past ten years. Construction of the forecast of the income and the definition of asymmetry was carried out based on the generalization of homogeneous phenomenons (million UAH and ten years). The average values were used to compare the obtained results, summarizing the characteristics of mass, qualitatively homogeneous socio-economic phenomenons, which scientifically predicted the main prospects. The results show a steady trend in the asymmetry of income asymmetry in Ukraine (both by type of economic activity and region), which will remain until 2024. In addition, it is found that Luhansk and Donetsk regions and the indicator (property income received) require additional research by surveying to establish the key risk factors.